Love in the Time of AIDS: Inequality, Gender, and Rights in South Africa - Hunter, Mark D. (Indiana University Press, 2010)
In some parts of South Africa, more than one in three people are HIV positive. Love in the Time of AIDS explores transformations in notions of gender and intimacy to try to understand the roots of this virulent epidemic. By living in an informal settlement and collecting love letters, cell phone text messages, oral histories, and archival materials, Mark Hunter details the everyday social inequalities that have resulted in untimely deaths. Hunter shows how first apartheid and then chronic unemployment have become entangled with ideas about femininity, masculinity, love, and sex and have created an economy of exchange that perpetuates the transmission of HIV/AIDS. This sobering ethnography challenges conventional understandings of HIV/AIDS in South Africa.